Rapamycin‐mediated mouse lifespan extension: Late‐life dosage regimes with sex‐specific effects. Issue 11 (4th November 2020) - Strong, Randy; Miller, Richard A.; Bogue, Molly; Fernandez, Elizabeth; Javors, Martin A.; Libert, Sergiy; Marinez, Paul Anthony; Murphy, Michael P.; Musi, Nicolas; Nelson, James F.; Petrascheck, Michael; Reifsnyder, Peter; et al.
Abstract: To see if variations in timing of rapamycin (Rapa), administered to middle aged mice starting at 20 months, would lead to different survival outcomes, we compared three dosing regimens. Initiation of Rapa at 42 ppm increased survival significantly in both male and female mice. Exposure to Rapa for a 3‐month period led to significant longevity benefit in males only. Protocols in which each month of Rapa treatment was followed by a month without Rapa exposure were also effective in both sexes, though this approach was less effective than continuous exposure in female mice. Interpretation of these results is made more complicated by unanticipated variation in patterns of weight gain, prior to the initiation of the Rapa treatment, presumably due to the use of drug‐free food from two different suppliers. The experimental design included tests of four other drugs, minocycline, β‐guanidinopropionic acid, MitoQ, and 17‐dimethylaminoethylamino‐17‐demethoxygeldanamycin (17‐DMAG), but none of these led to a change in survival in either sex. Abstract : Intermittent (1 month on/1 month off) or a limited 3‐month exposure to rapamycin, beginning at 20 months, was as effective as continuous exposure in increasing survival in males. In females, only intermittent exposure increased survival but the increase was not as great as continuous exposure.